Effect of Sub-Chronic Intermittent Ethanol Exposure on Spatial Learning and Ethanol Sensitivity in Adolescent and Adult Rats - Swartzwelder, H. S. (2014)
It has become clear that adolescence is a period of distinct responsiveness to the acute effects of ethanol on learning and other cognitive functions. However, the effects of repeated intermittent ethanol exposure during adolescence on learning and cognition are less well studied, and other effects of repeated ethanol exposure such as withdrawal and chronic tolerance complicate such experiments. Moreover, few studies have compared the effects of repeated ethanol exposure during adolescence and adulthood, and they have yielded mixed outcomes that may be related to methodological differences and/or secondary effects of ethanol on behavioral performance. One emerging question is whether relatively brief intermittent ethanol exposure (i.e., sub-chronic exposure) during adolescence or adulthood might alter learning at a time after exposure when chronic tolerance would be expected, and whether tolerance to the cognitive effects of ethanol might influence the effect of ethanol on learning at that time. To address this, male adolescent and adult rats were pre-treated with sub-chronic daily ethanol (five doses [4.0 g/kg, i.p.] or saline at 24-h intervals, across 5 days). Two days after the last pre-exposure, spatial learning was assessed on 4 consecutive days using the Morris water maze. Half of the animals from each treatment cell received ethanol (2.0 g/kg, i.p.) 30 min prior to each testing session and half of the animals received saline. Ethanol pre-exposure altered water maze performance in adolescent animals but not in adults, and acute ethanol exposure impaired learning in animals of both ages independent of pre-exposure condition. There was no evidence of cognitive tolerance in animals of either age group. These results indicate that a relatively short period of intermittent ethanol exposure during adolescence, but not adulthood, alters baseline water maze performance shortly after pre-exposure and does not induce cognitive tolerance to the effects of ethanol in either age group.